Initial rotor alignment method for doubly salient electromagnetic machine position sensorless startup. Issue 11 (1st May 2020) - Zhou, Xingwei; Zhou, Bo; Wang, Kaimiao
Abstract : The initial rotor alignment process plays an important role in 'align and go' which is a simple, implementable and widely industrial used position sensorless startup method. To deal with the possible jitter and reverse in the initial startup process, this Letter proposes a novel initial rotor alignment method for the position sensorless startup of the doubly salient electromagnetic machine (DSEM). According to the analysis of the generated electromagnetic torque, the relation between the alignment pulse and stable locating position is studied at first. Then, to improve the initial startup performance, the alignment pulse of switching on two upper transistors and one lower transistor is proposed to be injected as the alignment pulse since the stable locating position is around the middle point of rotor sector; it owns the benefit of better selection for the initial energising phase windings. The initial sensorless startup performance is desired to be improved in terms of no jitter or reverse. The experiments of initial alignment, as well as, the full process of the sensorless startup based on 'align and go' on a 12/8‐pole DSEM validate the flexibility and effectiveness of the proposed method.